MRE11 stability is regulated by CK2-dependent interaction with R2TP complex - von Morgen, P; Burdova, K; Flower, T G; O'Reilly, N J; Boulton, S J; Smerdon, S J; Macurek, L; Hořejší, Z (Oncogene, 2017)
The MRN (MRE11-RAD50-NBS1) complex is essential for repair of DNA double-strand breaks and stalled replication forks. Mutations of the MRN complex subunit MRE11 cause the hereditary cancer-susceptibility disease ataxia-telangiectasia-like disorder (ATLD). Here we show that MRE11 directly interacts with PIH1D1, a subunit of heat-shock protein 90 cochaperone R2TP complex, which is required for the assembly of large protein complexes, such as RNA polymerase II, small nucleolar ribonucleoproteins and mammalian target of rapamycin complex 1. The MRE11-PIH1D1 interaction is dependent on casein kinase 2 (CK2) phosphorylation of two acidic sequences within the MRE11 C terminus containing serines 558/561 and 688/689. Conversely, the PIH1D1 phospho-binding domain PIH-N is required for association with MRE11 phosphorylated by CK2. Consistent with these findings, depletion of PIH1D1 resulted in MRE11 destabilization and affected DNA-damage repair processes dependent on MRE11. Additionally, mutations of serines 688/689, which abolish PIH1D1 binding, also resulted in decreased MRE11 stability. As depletion of R2TP frequently leads to instability of its substrates and as truncation mutation of MRE11 lacking serines 688/689 leads to decreased levels of the MRN complex both in ATLD patients and an ATLD mouse model, our results suggest that the MRN complex is a novel R2TP complex substrate and that their interaction is regulated by CK2 phosphorylation.
Keywords: TOR Serine-Threonine Kinases; Phosphorylation; RNA Polymerase II; DNA-Binding Proteins; Heat-Shock Proteins; Humans; Cell Nucleus; enzymy opravy DNA; DNA vazebné proteiny; fosforylace; serin; teleangiektatická ataxie; oprava DNA; Protein Binding; TOR serin-threoninkinasy; mutace; jaderné proteiny; buněčné jádro; ATM protein; lidé; Casein Kinase II; zvířata; myši; DNA Repair Enzymes; Mice; DNA Repair; Apoptosis Regulatory Proteins; RNA-polymerasa II; Ataxia Telangiectasia; Ribonucleoproteins, Small Nucleolar; Nuclear Proteins; vazba proteinů; Ataxia Telangiectasia Mutated Proteins; kaseinkinasa II; proteiny regulující apoptózu; poškození DNA; DNA Damage; ribonukleoproteiny malé jadérkové; Animals; Mutation; Serine; proteiny teplotního šoku